ANALISIS KESALAHAN BERBAHASA BIDANG FONOLOGI SISWA SD SERTA PERAN GURU DALAM MENGATASINYA - Icha Meidayanti; Deri Anggraeni (JIPD (Jurnal Inovasi Pendidikan Dasar), 2024)
: Analysis of Language Errors in Elementary School Students' Phonology and the Role of Teachers in Overcoming Them. This research aims to analyze language errors phonology of SD N Bangunjiwo students and the role of teachers in overcoming them. The method used is a descriptive method with data collection techniques through observation and interviews with grade 3 students at SD N Bangunjiwo. The research results show that there are several phonological errors that are commonly made by students, such as phoneme substitution, phoneme deletion, and phoneme addition. In addition, the teacher's role in overcoming students' phonological errors is very important. Teachers need to pay special attention, through interesting learning methods, appropriate exercises, and constructive feedback. Thus, it is hoped that students can correct their phonological errors. It is hoped that this research can contribute to efforts to improve the quality of Indonesian language learning at the elementary level. Keywords: language errors, phonology, elementary school students, the role of the teacher.